Intelligent device for diagnosis of dam's condition - Savrasov F. V. Fedor Vitalievich; Shamin A. A. Aleksey Alekseevich; Pershin E. A. Evgeny Andreevich; Meyta R. V. Roman Valerjevich; Moiseev A. N. Anton Nikolaevich (2016, 2016)
Title screen